Na XVI s'yezde VKP postavlena pervoocherednaya zadacha sozdat' 2-yu ugol'no metallurgicheskuyu bazu (Государственное иедательство (ОГИЗ), 1930)
Images of All-Russian Communist Party politicians including Stalin speaking amid paintings of workers marching, coal mining, and steel forging Original title: На XVI с'езде ВКП поставлена первоочередная задача создать 2-ю угольно металлургическую базу. Suggested translation: At the 16th congress of the VKP(B): The first task is to create a 2nd coal and metallurgical base PO-0026